2014
DOI: 10.1155/2014/518920
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Obstructive Sleep Apnea Syndrome, Continuous Positive Airway Pressure Treatment, and Inflammatory Cytokines

Abstract: The cardiovascular complications that frequently accompany obstructive sleep apnea syndrome (OSAS) are thought to develop as a result of inflammatory stress associated with cytokines such as IL-6 and TNF-α. We conducted the current study to compare levels of these cytokines in OSAS patients (n = 33) and nonapneic controls (n = 24). Furthermore, we investigated the impact of a three-month regime of continuous positive airway pressure (CPAP) on serum levels of IL-6 and TNF-α only in the OSAS patients. There were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…Our study targeted patients with OSA and investigated the relationship between fatigue severity and sleep related factors and identified the factors that affect fatigue severity. Some studies have demonstrated that the proinflammatory cytokines like IL‐6 and/or TNF‐alpha are elevated in disorders associated with OSA and fatigued patients . Thus this point might have relevance to linkage between OSA and fatigue in biochemical basis.…”
Section: Discussionmentioning
confidence: 93%
“…Our study targeted patients with OSA and investigated the relationship between fatigue severity and sleep related factors and identified the factors that affect fatigue severity. Some studies have demonstrated that the proinflammatory cytokines like IL‐6 and/or TNF‐alpha are elevated in disorders associated with OSA and fatigued patients . Thus this point might have relevance to linkage between OSA and fatigue in biochemical basis.…”
Section: Discussionmentioning
confidence: 93%
“…[ 25 ] Results from previous studies on potential links between these cytokines, OSAS, and CPAP therapy, have been conflicting, possibly generated from the fact that cytokine levels are influenced by a number of factors, such as inflammatory diseases including hypertension per se, life styles such as smoking, and some medications and the difference in subjects. [ 26 ] In this study, grate care was given to match groups in terms of basic characteristics to establish the role of OSA. Thus, the limited sample size, small BMI ranges, normal blood glucose and age and potential effects of hypertension may explain the similarity on IL-6 and TNF-α in levels.…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 and TNF-α levels were examined in a study of 33 OSA patients and 24 non-apneic, Body Mass Index (BMI)-matched controls as well as the impact of 3 months of CPAP therapy. At baseline, no differences in IL-6 or TNF-α were observed, nor any changes in the mean level of these cytokines with CPAP therapy [52]. Kritikou et al examined 24-hour profiles of IL-6, TNF-α receptor-1, leptin, adiponectin, hsCRP, glucose, and insulin in 77 middle-aged subjects.…”
Section: Osa and Inflammation – Recent Clinical Findingsmentioning
confidence: 99%